Evaluation of Wastewater Treatment Installations at Kendari City Hospital - Ranno Marlany Rachman; Pidun Pidun; Romy Talanipa (Jurnal Ilmu Lingkungan, 2025)
Hospitals are public facilities that generate large amounts of waste from various activities, including liquid waste containing hazardous substances that must be treated before discharge into the environment. This study aims to evaluate the performance of the Kendari City Regional Hospital Wastewater Treatment Plant (WWTP) and to determine the quality of wastewater after treatment, in accordance with the Minister of Environment Decree Number 5 of 2014. This study uses a quantitative descriptive method with an observation approach, laboratory testing, and interviews. The results of the survey in August 2023 showed that the Kendari City Regional Hospital WWTP functioned effectively with a significant decrease in several parameters, namely pH by 1.40%, TSS (Total Suspended Solids) by 68.00%, COD (Chemical Oxygen Demand) by 51.10%, and BOD (Biochemical Oxygen Demand) by 86.70%, while the temperature did not change. In December 2023, the wastewater treatment plant's effectiveness was still not optimal, with a pH of 9.38%, TSS of 21.4%, COD of 31.1%, BOD of 32.7%, and a temperature increase of 5.27%. The effluent from Kendari City Hospital in August 2023 met the quality standards set by the Minister of Environment Decree Number 5 of 2014, with a temperature of 28°C, pH of 7.34, TSS of 71 mg/L, COD of 18.70 mg/L, and BOD of 1.50 mg/L. However, in December 2023, although the effluent still met most quality standards—pH 6.76, TSS 22 mg/L, COD 23.8 mg/L, and BOD 10.7 mg/L —the temperature was 31.1°C, exceeding the set quality standard limit of 30°C.